Characterization of RF Noise in UTBB FD-SOI MOSFET - Pragya Kushwaha; Avirup Dasgupta; Yogendra Sahu; Sourabh Khandelwal; Chenming Hu; Yogesh Singh Chauhan (IEEE Journal of the Electron Devices Society, 2016)
In this paper, we report the noise measurements in the RF frequency range for ultrathin body and thin buried oxide fully depleted silicon on insulator (FD-SOI) transistors. We analyze the impact of back and front gate biases on the various noise parameters; along with discussions on the secondary effects in FD-SOI transistors which contribute to the thermal noise. Using calibrated TCAD simulations, we show that the noise figure changes with the substrate doping and buried oxide thickness.